Evaluation of Summer Stress Mitigation Strategies through Plasma Cortisol, Oxidative Markers and Conception Rates in Jaffarabadi Buffaloes (Bubalus bubalis) - Borakhatariya, Devasee N; Vala, Karshan B; Vijyeta, Hardeep P; Karangiya, Vijay K; Singh, Vivek K; Patbandha, Tapas (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The current study was executed on postpartum (45-60 days) Jaffarabadi buffaloes from March to June 2023 (summer season), aimed  at ascertaining how summer stress mitigation protocols affect conception rates and different biomarkers associated with oxidative  stress of summer. The open animals were subjected to timed artificial insemination (TAI) Ovsynch protocol of estrus induction cum  synchronization, and responded 24 buffaloes were randomly assigned to four different treatment/mitigation protocols or groups after  AI (n=06 per protocol), viz., the NSAID protocol, the antioxidant protocol, the P4 protocol, and a control group. The percent conception  rates at 35th day (USG) and at 60th day (per rectal palpation) in buffaloes under four groups were 50.00 and 0.00 %, 50.00 and 33.34%,  16.67 and 16.67%, and 16.67 and 16.67%, respectively, indicating embryonic loss between day 35 and 60 post-AI to the extent of 100%  and 33.34% in NSAID and antioxidant treated groups, respectively, and nil in other two groups. The overall mean cortisol concentration  was significantly (p
Keywords: Embryonic loss; Heat stress; MDA; Oxidative stress; Summer season; TAC